Integration of Forestry Crops with Agricultural Crops Through Agroforestry Business Patterns in Central Lombok District - Husni, Syarif; Wangiyana, Wayan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Agroforestry can be successful if it can increase people's income while maintaining land productivity. Research objectives: 1). knowing the pattern of agroforestry farming in North Batukliang District, 2). analyzing income, business efficiency and rice-equivalent farmer income in various agroforestry farming patterns in North Batukliang District. a total of 43 people were determined by dividing members of the population into several subgroups called starta, then a sample was selected from each stratum using the Stratified Random Sampling method. The results of the research show: 1) There are two agroforestry farming patterns implemented by HKm farmers in North Batukliang District, Central Lombok Regency, namely Pattern I is dominated by MPTS (Multy Purpose Tree Species) crops and Pattern II is dominated by annual crops, 2) Farmer income in pattern I is dominated MPTS (Multy Purpose Tree Species) plants amounting to Rp. 9,133,036/ha/year and income of pattern II farmers dominated by annual crops of Rp. 6,995,800/ha/year, 3) Pattern I agroforestry farming efficiency level is 3.56 and Pattern II is 2.96, and 4) Income farmers measured in rice equivalent is 911.33 kg per year for Pattern I and Pattern II is 699.68 kg.